Detection of discretized single-shell penetration in mesoscopic vortex matter - Dolz, M. I. (2014)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina